Analisis Dampak Pembangunan Bendungan Beringin Sila Terhadap Pola Tanam Dan Pendapatan Petani Di Kecamatan Utan, Kabupaten Sumbawa - Hidayanti, Indah Octa; Jufri, Akhmad; wijimulawiani, Baiq Saripta (Universitas Mataram, 2024)
This research aims to (1) analyze the impact of the construction of the sila banyandam in Utan district on planting patterns (2) anlyze the impact of the construction the sila banyan dam on farmers’ income. The total population is 167 and the sample size is 45 people. This research uses quantitive and qualitative methods with data collection techniques, namely survey or interview techniques. The result of the reaserch show that the prescence of the sila banyan dam has changed the planting patterns in Utan Sub-district. Before BBS, the planting patterns was rice-corn. And after BBS, the planting changed to rice-corn-corn. In terms of income, in the orong baru and orong stukal areas after the existence of the sila banyan dam, farmers icome was higher than before BBS. Meanwhile, in the orong rangintan area after the sila banyan dam was established, there was no difference in farmers’ income after BBS.‎ hasil penelitian menunjukkan adanya bendungan beringin sila telah merubah pola tanam dikecamatan utan. sebelum adanya bendungan beringin sila, pola tanamnya yakni Padi-Jagung. sedangkan setelah adanya bendungan beringin sila, pola tanam petani berubah menjadi Padi-Jagung-jagung. Dilihat dari segi pendapatan petani lebih tinggi dibandingkan sebelum BBS. Sedangkn pada wilayah orong rangintan setelah adanya BBS, tidak ada perbedaan pendapatan petani sesudah BBS.